Secular Drivers of the Natural Rate of Interest in the United States : A Quantitative Evaluation - Platzer, Josef (IMF Working Papers; Working Paper ;, 2022)
We develop a heterogeneous agent, overlapping generations model with nonhomothetic preferences that nests several explanations for the decline in the natural rate of interest (r*) suggested in the literature: demographic change, a slowdown in productivity growth, a rise in income inequality, and public policy. The model can account for a 2.2 percentage point (pp) decline in r* between 1975 and 2015, which is within the range of empirical estimates. Rising income inequality is an important driver (-0.70 pp), and together with demographic change (-0.71 pp) and the slowdown in productivity growth (-1.0 pp) explains most of the decline. Growing public debt is the major counteracting force (+0.31 pp). Permanent income inequality is of greater importance than inequality due to uninsurable income risk, and matching the degree of nonhomotheticity in consumption and savings behavior to empirical estimates is essential for this result. We predict that r* will reach a low of 0.38% by 2030, after which a slow reversal will begin. The natural rate will stabilize at 1% in the long run, a low level when compared with the postwar path of r* implied by the model. This remains true even if we take into account soaring public debt levels due to the COVID-19 pandemic. Policy can have considerable impact on the level of r* through the tax and transfer system.